Influence of vocal effort on average and variability of fundamental frequency - Jessen, Michael; Koster, Olaf; Gfroerer, Stefan (International Journal of Speech, Language and the Law, 2005)
Read and spontaneous speech was produced by 100 male adult speakers of German in a neutral setting and in a Lombard setting, where 80 dB noise was presented over headphones. Average f0 (‘f0mean’) and relative standard deviation of f0 (‘f0varco’) were determined for each speaker in each of the four conditions spontaneous neutral, spontaneous loud, read neutral and read loud. The results confirm thatwhen increasing vocal effort from neutral to loud speech, f0mean increases as well.None of the 100 speakers posed an exception to this effect, but the size of the effect differed between speakers, even after differences in amplitude level were accounted for. F0varco was significantly higher in loud than normal speech for the reading task, whereas in spontaneous speech no significant difference occurred. These results are compared with the literature and discussed with respect to explanations and forensicphonetic implications.